LANGUAGE INSTRUCTORS’ PERCEPTIONS OF L2 SKILL ACQUISITION WITH ONLINE EDUCATIONAL TECHNOLOGY DURING COVID 19 - MCQUEEN, OLIVER GILES (2021)
This dissertation aims to dissect the perceptions of English instructors and their understanding of how the global pandemic and advancement of Educational Technology (EdTech) has impacted L2 acquisition. Theorists such as Skinner (1957), Chomsky (1959), Krashen (1988) and Vygotsky (1980) have critically examined effective strategies in which L2 acquisition can be applied. As a result, this dissertation draws upon these views and connects them with the perceptions of highly educated working professionals, who teach in the field of TESOL, thus providing valuable feedback on achievable, insightful and progressive strategies that can be implemented within the UAE Educational System. The findings from this research may help in understanding the pedagogical methods that teachers apply in their teaching. It provides a cross analysis of both qualitative and quantative data in order to assess the current changes taking place during Covid 19. This is significant, as teachers are the keys to learning. They are often overlooked, overworked and neglected when making important decisions within the field of education. Therefore, this dissertation attempts to capture their personal views at a time of much change, allowing for a deeper understanding of teaching methodology that transcends the four walls of the classroom. Adding to the already, well established frameworks of L2 acquisition, adding value where required, from experienced teachers, will undoubtedly be a means for students, and parents to learn from and essentially provide better ideas for overall school improvement (Knapp, 1997).